GROWTH AND DEVELOPMENT CHARACTERISTICS OF WEIGELA FLORIDA AT DIFFERENT ONTOGENETIC STAGES UNDER THE CLIMATIC CONDITIONS OF THE ANDIJAN REGION (Modern American Journal of Engineering, Technology, and Innovation, 2026)
This article analyzes the introduction history of Weigela florida and the characteristics of its growth and development at different ontogenetic stages under the climatic conditions of the Andijan region. The study examines the dynamics of the vegetation period, including the onset of vegetation, the phase of active growth, leaf formation and their morphometric parameters, as well as leaf fall processes. In addition, scientific data on the morphological features of the root system, the stages of budding and flowering, fruit formation, and ripening are presented.Based on the obtained results, the adaptive characteristics of the species to local climatic conditions are evaluated, and the prospects for its use in landscaping are substantiated.